JUDUL TIDAK TERCANTUM DALAM BAHASA INGGRIS - MAGRIBI SADLI (NIM : 10212090), AL
Geolectrical resistivity method is part of geophysical methods that used the flow of electricity below the earth surface. Geoelectrical resistivity method can describe the subsurface of the earth based on variation of resistivity of rock. In this research geoelectrical resistivity method is used to identify the distribution of andesite. 1D inversion of geoelectrical data is applied for schlumberger configuration field data using singular value decomposition method on 3 profiles. The 1D inversion modeling results are compared with 2D inversion modeling results. The result of the modeling have shown that there are 3 layers where the 2nd layer is more conductive compared to the others. The existing of the andesite is identified on the 3rd layer with the high resistivity (> 180 ohm.m) located at the depth of 5 Ã‚Â– 15 meter from the surface. This result is a good agreement with the geological and borehole data.